VERBAL TECHNIQUES FOR MAINTAINING A CONVERSATION IN ENGLISH AND VIETNAMESE - Trịnh Ngọc Xuân Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study aims to assist learners to get an awareness of how English and Vietnamese conversations are verbally maintained. Besides, they are expected to recognize the similarities and differences of the techniques used between the two languages. Simultaneously, the pedagogical recommendations set forth by the end of this study will partly contribute to the teaching and learning of English, especially in conversation.